(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
The main drawbacks associated with any existing steganography systems are, one, the distortion happens to the apparent view of the wrapper image after embedding and second the fewer hiding capacity of stego-image. When the confidential data is miniscule the system would be perfect. However, when the amount of secret data increases the disturbance caused is perceptible. Our aim with this proposed technique is to implement a stego system that gives maximum payload capacity with improved viscinity of the stego- image. With the slated objectives the proposed work try to maximize the security with high payload by enhancing the apparent view of the image so as to give no trace of hidden secret inside the cover.We propose a multi level security approach that uses visual cryptography for encryption to achieve security at first level and a brand new steganography method called Selected Matrices Pixels LSB [SMPLSB] at next level. In contrast to the distortion happens when hiding data inside a digital image, the projected technique enhances the host image quality while embedding. It finds a trivial location or less sensitive traits of the cover to embed the secret and make sure that embedding does not affect the original view of the image. The steps are repeated until the whole secret is hidden without disturbing the original view. Cover image preprocessing is also done to make the cover best suit for embedding.Our proposed approach cut short the chance ofsteg-analysis. It keeps a position map to assure the accurate fetching of hidden message. Higher PSN ratio of 50.1 dB, SSIM value of 1 and AAD 0.15050 show the projected method achieves good security with large payload .